The ability to increase milk production in cows of local breeds - Войтенко, С. Л. (Scientific Progress & Innovations, 2016)
The article highlights the results of studies on the impact of factors on milk production of cows of Ukrainian whitehead breed, which belongs to a local dairy breeds productivity and kept only one breeding sector. Formation of milk production of cows of the breed consistent with animal origin and serial number of lactation. Lines Marta 171 and 417 Ozona respectively 4483,1 and 4254,9 kg of milk for signs of variation in terms of lines within 3976,4–4483,1 kg are characterized the highest yields for the first 305 days of lactation cows. It was found that the yield of the plant herd of cows is increased to 5–6 lactation, allowing to increase the duration of the economic use of more productive cows while maintaining the genetic trait variability. On the possibility of increasing the milk yield of cows breeding methods indicates the coefficient of variation of milk yield of cows lines studied, except Zharguna 157. Consequently, the increase of milk productivity of cows of the Ukrainian whitehead breed, you can implement the methods of inbreeding selection, keeping the gene pool of the local national population of cattle.